Is there a transfer of postural ability from specific to unspecific postures in elite gymnasts? - Asseman, F.; Caron, O.; Cremieux, J. (Neuroscience Letters, 2004)
The purpose of this study was to investigate the transfer of postural ability by comparing the level of performance and postural control of eliten gymnasts in postures specifically trained or not. Fifteen elite gymnasts were asked to stand as still as possible with eyes opened in three conditions: bipedal, unipedal and handstand. Surface and mean velocity of the centre of pressure motions were used to quantify respectively performance and postural control. A ranking was made for each parameter to determine the level of each subject. As a whole, the subject's level of postural performance and control in one condition was not correlated to the corresponded level in another condition. Therefore, postural ability of elite gymnasts in the handstand is not transferable to upright standing postures.